2010
DOI: 10.1063/1.3311884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon addition on the single crystalline magnetostriction of Fe-X (X=Al and Ga) alloys

Abstract: The effect of carbon addition on the magnetostriction of Fe-Ga and Fe-Al alloys was investigated and is summarized in this study. It was found that the addition of carbon generally increased the magnetostriction over binary alloys of Fe-Ga and Fe-Al systems. The formation of carbide in the Fe-Ga-C alloys with a composition near D0 3 phase region decreased the magnetostriction drastically. Fe-Al-C and Fe-Ga-C alloys responded differently to thermal treatments; the magnetostriction in the quenched Fe-Al-C alloys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
1
8
0
2
Order By: Relevance
“…4 insets. The saturation magnetization at 300 K of the Fe 80 Al 20 alloy sample was observed to be 187 Am 2 /kg, which is in good agreement with values reported by the authors of [20,21], who reported 189 Am 2 /kg for a Fe 81 Al 19 alloy and 185 Am 2 /kg for a Fe 80 Al 20 alloy, respectively. The and Fe 2 B such that M S cubic phases > M S Fe2B [28].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…4 insets. The saturation magnetization at 300 K of the Fe 80 Al 20 alloy sample was observed to be 187 Am 2 /kg, which is in good agreement with values reported by the authors of [20,21], who reported 189 Am 2 /kg for a Fe 81 Al 19 alloy and 185 Am 2 /kg for a Fe 80 Al 20 alloy, respectively. The and Fe 2 B such that M S cubic phases > M S Fe2B [28].…”
Section: Resultssupporting
confidence: 92%
“…The Fe 3 Al phase is the majority phase in the alloy without boron, with a proportion of 39:1 of Fe 3 Al: a -FeAl, whereas in the sample with 2% of B, the proportion is 2:1. This result indicates that boron is actually functioning as ana-phase stabilizer, thereby changing the solubility limit of the A2 and D03 phases as suggested in[20].InFig. 3, the evolution of the lattice parameter of the Fe 3 Al (D03) and a -FeAl phases is shown as a function of the amount of boron added to the Fe 80 Al 20 alloy.…”
mentioning
confidence: 68%
“…Since the discovery of single crystal Fe-Ga and Fe-Ga-X alloys, with saturation magnetostriction values of $432 ppm along h100i orientation, other Fe-based alloys with useful tetragonal distortions, (3/2)k 100 , are also receiving increasing attention, e.g., Fe-Al and Fe-Co alloys. [1][2][3] The crystal structure and magnetostriction trends of Fe-Al alloys are similar with those of Fe-Ga alloys. 4,5 Both alloys exhibit peak h100i magnetostriction values at $20 at.…”
mentioning
confidence: 56%
“…In recent years, alloying elements were added into Fe-Ga alloys to improve the magnetostrictive performance and the mechanical properties. It is reported that the trace amounts of C, B, and N atoms have a beneficial effect on the magnetostriction of Fe-Ga single crystals [6][7]. These atoms may enter into octahedral sites as in pure α-Fe and prevent the formation of DO 3 phase, resulting in increased magnetostriction of Fe-Ga alloys when the Ga content exceeds 18at%.…”
Section: Introductionmentioning
confidence: 95%